Factores socioculturales y abandono de la lactancia materna exclusiva en madres con lactantes de la institución Prestadora de Servicios de Salud I-3 Túpac Amaru Iquitos 2025 - Sales Ruiz, Johana del Fatima (2025)
To determine the relationship between sociocultural factors and the abandonment of exclusive breastfeeding in mothers with infants from the Health Service Provider Institution I-3 Tupac Amaru Iquitos 2025. This is a quantitative, non-experimental, descriptive, correlational, and cross-sectional study; the population consisted of 52 mothers with breastfed children under six months of age. The results obtained were: of the social factors: 73.1% are cohabitants, 48.1% have completed secondary school, 90.4% are from urban origin, 61.5% are part of extended families, and 71.2% are housewives; of the cultural factors: in 57.7% myths and beliefs do not prevail, 80.8% have adequate knowledge, 59.6% have family support. 40.4% of breastfed children under six months of age were not exclusively breastfed. There was a significant correlation between educational level (0.008 using the chi-square test) and origin (0.050 using the Fisher exact test); there was no significant correlation between marital status (p=0.421), family type (p=0.602), occupation (p=0.278), myths and beliefs (p=0.523), knowledge (p=0.144), and family support (p=0.394). It was concluded that social and cultural factors such as marital status, family type, occupation, myths and beliefs, and family knowledge and support are negatively contributing to the abandonment of exclusive breastfeeding.